The impact of two-dimensional perfectionism on burnout and eating disorders in young Finnish athletes : comparison between males and females - Sorkkila, Matilda (2014)
Matilda Sorkkila, 2014. The impact of two-dimensional perfectionism on burnout and eating disorders in young Finnish athletes: comparison between males and females. Master’s Thesis in Sport and Exercise Psychology. Department of Sport Sciences. University of Jyväskylä. 40 p.